Wavelet Analysis on FECG Detection Using Two Electrodes System Device - Jamaluddin, Fauzani N.; Bakti, Zulkifli Abdul Kadir; Kamal, Mustaffa; Aminudin, Azan (International Journal of Integrated Engineering, 2014)
Fetal electrocardiogram (FECG) signal detection during pregnancies is very useful in assessing fetal condition. Doppler ultrasound is very common in non-invasive FECG detection. It is safe, but inaccurate, highly sensitive to noise and the success of the measurement depends on the positioning of the probe. Recently, there are many research use non-invasive Ag/AgCl in FECG detection. However it involves large number of electrode during measurement. In addition, complex structures of signal processing are required. A study has been made on FECG detection using two electrodes biopotential device without reference electrode. Best possible electrode placement for maximum FECG waveforms detection has been identified. The FECG signals are successfully detected at 0.028Hz after processed using wavelet analysis.